UPAYA KEBERATAN NOTARIS TERHADAP MAJELIS KEHORMATAN NOTARIS WILAYAH ATAS DISETUJUINYA PERMINTAAN PENYIDIK, PENUNTUT UMUM DAN HAKIM DALAM PROSES PERADILAN - LAYLA MAYSAROH (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Suprayitno3. Madiasa Ablizar Notary is a general official authorized to make authentic deeds as stipulated in the format and content based on the prevailing laws and regulations in the field of authentic deed making in general and authentic notary deeds in particular. The type of research used in this study is normative legal research. The nature of this research is analytical descriptiv. The results of the discussion of the problems that arise in this study is the arrangement of the regional notary honorary assembly in providing answers to approval at the request of investigators, public prosecutors and judges in the judicial process as stipulated in the Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning Notary Honorary Assembly. Conduct self defense where in the examination conducted by the examining body formed by the notary regional council chairman and the notary can make other legal remedies by filing an objection to the request of the investigator in the judicial process that is given by the notary honor council to the local State Administrative Court. Keywords : Honorary Council of Notaries, Investigators, Public Prosecutors and Justice